1946
DOI: 10.1002/j.1537-2197.1946.tb10379.x
|View full text |Cite
|
Sign up to set email alerts
|

Development in Sterile Culture of Stem Tips and Subjacent Regions of Tropaeolum Majus L. And of Lupinus Albus L

Abstract: THEORETICALLY, the shoot apex of higher plants that length rooted only in light. Large plants were should prove the ideal object for experimental mor-grown from these cultures. Smith (1940) grew stem phology. It produces by its activities tissues from tips (0.55 to 4.0 mm, long) of Helianthus annuus which all the vegetative parts of the shoot are dif-on agar in White's solution. Studies were made of ferentiated. The problems of differentiation, or ma-the effects of various accessory growth factors in turation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1948
1948
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In an elegant experiment, Ball (1980) demonstrated that shoot apices of blue lace flower (Trachymene coerulea) regenerated into whole plants in vitro on culture medium without exogenous growth regulators. In earlier studies with Tropaeolum majus and Lupinus albus he discovered that no exogenous growth substances were required if the explant consisted of the apical meristems together with two or more pairs of primordial leaves (Ball 1946(Ball , 1960. Since plant cells do not generally grow in the absence of hormones, the plant regeneration noted here is attributable to the hormones synthesized in the cowpea explants, by the primordial leaves.…”
Section: Results and Discussion Soybeanmentioning
confidence: 99%
“…In an elegant experiment, Ball (1980) demonstrated that shoot apices of blue lace flower (Trachymene coerulea) regenerated into whole plants in vitro on culture medium without exogenous growth regulators. In earlier studies with Tropaeolum majus and Lupinus albus he discovered that no exogenous growth substances were required if the explant consisted of the apical meristems together with two or more pairs of primordial leaves (Ball 1946(Ball , 1960. Since plant cells do not generally grow in the absence of hormones, the plant regeneration noted here is attributable to the hormones synthesized in the cowpea explants, by the primordial leaves.…”
Section: Results and Discussion Soybeanmentioning
confidence: 99%
“…Morphogenesis from shoot apices of L. albus was first described by Ball (1946). Occasionally, shoot regeneration has also been obtained from leaf explants of L. luteus (Sator 1985a) and from nodal segments of L. albus, L. angustifolius and L. luteus (Schafer-Menuhr 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Plantlets were successfully produced by culturing shoot tips with a couple of primordia of Lupinus and Tropaeolum [9], but the importance of this finding was not recognized until later when this approach to obtain virus-free orchids, its potential for clonal propagation was realized [49]. The potential was rapidly exploited, particularly with ornamentals [50].…”
Section: The Development and Improvement Of Techniquesmentioning
confidence: 99%
“…Such root cultures were used initially for viral studies and later as a major tool for physiological studies [7]. Success was also achieved with bud cultures [8,9].…”
Section: Introductionmentioning
confidence: 99%